If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + -22 = -15 + 4y Reorder the terms: -22 + 5y = -15 + 4y Solving -22 + 5y = -15 + 4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4y' to each side of the equation. -22 + 5y + -4y = -15 + 4y + -4y Combine like terms: 5y + -4y = 1y -22 + 1y = -15 + 4y + -4y Combine like terms: 4y + -4y = 0 -22 + 1y = -15 + 0 -22 + 1y = -15 Add '22' to each side of the equation. -22 + 22 + 1y = -15 + 22 Combine like terms: -22 + 22 = 0 0 + 1y = -15 + 22 1y = -15 + 22 Combine like terms: -15 + 22 = 7 1y = 7 Divide each side by '1'. y = 7 Simplifying y = 7
| 15x=5x | | 9x+15-8x=-2-10 | | 4x=15x | | 9n-8=-20+3n | | 4x=2(6x+16) | | -8(-8x-6)=6(5x+4) | | 4x+14-3x=-5-10 | | -5(x+1)-13=10+2 | | 6x=2(8x+20) | | (2x+4)(x-5)=0 | | 5p=-40-33p | | 15x-29y=429 | | 4x^2-16x+5= | | 4P=7(7P+3) | | 4(3+2x)-3=49 | | x+13x=-40 | | 5y+3=-5 | | 3x^2-9x+27=0 | | 2x-8x+6=-19 | | 4x+8=20x+1 | | 70+20x=350 | | 4x+2=20x+1 | | -3+4x=-1-6x | | 1x+1x+48=3x+5x | | 7x+4/3=2x-1 | | x^2+10=-16 | | 9x^2-12x-3=0 | | -6x+12=4x-8 | | 9x^2-12-3=o | | -(x+3)=-(x+2)-2 | | x+2y=-9 | | n/3=10 |